Effect of Impaired T Cell Receptor Signaling on the Gut Microbiota in a Mouse Model of Systemic Autoimmunity. Issue 4 (25th February 2022) - Shirakashi, Mirei; Maruya, Mikako; Hirota, Keiji; Tsuruyama, Tatsuaki; Matsuo, Takashi; Watanabe, Ryu; Murata, Koichi; Tanaka, Masao; Ito, Hiromu; Yoshifuji, Hajime; Ohmura, Koichiro; Elewaut, Dirk; et al.
Abstract : Objective: T cell receptor (TCR) signaling abnormalities and gut dysbiosis are thought to be involved in the development of systemic lupus erythematosus (SLE). However, it is not known whether these mechanisms are interrelated. This study was undertaken to explore the impact of defective TCR signaling on microbiota‐driven immune responses and the consequent triggering of systemic autoimmunity. Methods: The responses of B6SKG mice harboring a mutation in ZAP‐70 leading to spontaneous development of SLE were evaluated under specific pathogen–free (SPF) and germ‐free (GF) conditions. The gut microbiome was analyzed using 16S ribosomal RNA sequencing. Secretory IgA production in the gut and follicular helper T (Tfh) cell development in the spleen and Peyer's patches were analyzed. Interleukin‐17 (IL‐17)–deficient mice and segmented filamentous bacteria (SFB)–specific TCR‐transgenic mice were used to examine the role of IL‐17 and thymic selection. Results: SLE development in B6SKG mice was significantly more attenuated under GF conditions than under SPF conditions. The gut microbiota in B6SKG mice was altered, which was associated with the expansion of SFB and consequent development of SLE by driving Th17 cell differentiation, which was in turn blunted by IL‐17 deficiency. Notably, although systemic Tfh development and autoantibody IgG response were enhanced, local gut Tfh and IgA responses were impaired. Moreover, experiments in SFB‐specific TCR‐transgenic mice revealed that this differential response was caused by altered thymic selection of self‐ and microbiota‐reactive TCR because of defective TCR signaling. Conclusion: Our findings indicate that defective TCR signaling alters the gut microbiota and promotes systemic autoimmunity by driving Th17 cell differentiation.